(untitled) (Análisis Económico, 2018)
Los sistemas de producción de chile manzano (Capsicum pubescens R y P) en México son de campo abierto bajo sombra de árboles de pino y frutales de temporada, e intensivo en hidroponía bajo condiciones de invernadero. Estos sistemas presentan diferencias significativas en los aspectos técnicos, financieros y comerciales como consecuencia de las innovaciones tecnológicas y por el grado de inversión de capital. Técnicamente el sistema intensivo bajo condiciones de invernadero es el más eficiente, ya que permite un control más eficiente de los factores ambientales, incidencia de plagas, enfermedades y polinización. Además, la vida productiva del cultivo es mayor y se obtienen rendimientos elevados en pequeñas superficies. Los indicadores financieros considerados en el estudio señalan que los sistemas evaluados fueron económicamente rentables. Comercialmente, el chile manzano producido en cualquier sistema no presenta problemas para su venta en los mercados regionales y nacionales. En este sentido el producto de invernadero presenta ventajas comparativas y competitivas respecto del de campo. Por otra parte, se detectó que los agentes que intervienen en la comercialización limitan la participación del productor en el precio de venta final. Clasificación JEL: Q13. Abstract Manzano hot pepper (Capsicum pubescens R y P) production in México in did under three different systems: under open field conditions with the use of pine trees for shade protection, under open field conditions with the use of fruit trees for shade protection, and under intensive greenhouse conditions using hydroponics. There are significant technical, financial and commercial differences between these systems as the result of technological innovation and greater capital investment of hydroponics. The most efficient systems, from the technical point of view, is the one under intensive greenhouse conditions, since it implies better control of environmental factors, pests, disease and pollination. Besides, the intensive greenhouse system lengthens the productive life span of hot peppers and makes for higher yields in smaller areas. The financials indicators that were used also show that the three systems are economically sound. Commercially, it is not difficult to market red hot manzano pepper produced by any of the three systems at the regional and national level, buy fruit quality is a crucial factor for the consumer international markets. In this sense the greenhouse product is superior to the open field products since it has comparative and competitive advantages. On the other hand, this research revealed that the people who are involved in the marketing of manzano hot peppers limit the agricultural producers´ participation in establishing final market prices.